2015 Seventh International Conference on Knowledge and Systems Engineering (KSE) 2015
DOI: 10.1109/kse.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis for Vietnamese Dependency Parsing

Abstract: Dependency parsing is needed in different applications of natural language processing. In this paper, we present a thorough error analysis for dependency parsing for the Vietnamese language, using two state-of-the-art parsers: MSTParser and MaltParser. The error analysis results provide us insights in order to improve the performance of dependency parsing for the Vietnamese language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…In our experiments, we use the VnDT [15] which has 10,200 dependency structures. For comparison purposes, we split the data in the same way as [18], last 1020 sentences for testing (POS and automatic POS tagging) and the rest for training. The POS tagging tool we used is VnTagger 1 , its accuracy is 94.4% on our test set.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experiments, we use the VnDT [15] which has 10,200 dependency structures. For comparison purposes, we split the data in the same way as [18], last 1020 sentences for testing (POS and automatic POS tagging) and the rest for training. The POS tagging tool we used is VnTagger 1 , its accuracy is 94.4% on our test set.…”
Section: Resultsmentioning
confidence: 99%
“…We found that [18] did not incorporate pre-trained word embeddings in the vector representation of words. Although this feature can improve the accuracy of dependency parsing because of its rich context information [11] [12] and [17].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, Mandar Joshi and co-authors [22] proposed pair2vec model exploiting surface form of contexts instead of dependency paths. From the review of previous studies in subsection 1.1, there are still two open problems as follows: -Using neural network models to exploit cooccurrence contexts of word pairs without relying on syntactic parse trees: For low-resource languages like Vietnamese, syntactic parsers can only achieve an accuracy much lower than those for English [23]. Table 1 shows a number of word length statistics from a popular Vietnamese dictionary conducted by Nguyen and co-authors [24].…”
Section: A Summary Of Our Workmentioning
confidence: 99%
“…According to the error analysis results for Vietnamese dependency parsing in [12], dependency parsing tends to have lower accuracies on long dependencies. We can see that a lot of dependency relations (noun modifier, verb modifier, subject, direct object, root, adjective modifier, coordination, conjunction, indirect object) have lower accuracies than others, as shown in Table I (the figures in this table are from the paper [12]). Therefore, we focus on finding new features to solve above problems related to these dependency relations.…”
Section: B Vietnamese Dependency Parsingmentioning
confidence: 99%